Raybearer - Ifueko, Jordan (Amulet Books, 2020)
Raised in isolation, Tarisai yearns for the closeness she could have as one of the Crown Prince's Council of 11, but her mother, The Lady, has magically compelled Tarisai to kill the Crown Prince.